GAMBARAN STATUS GIZI DAN PRESTASI SISWA SEKOLAH MENENGAH ATAS - Dilla Fadlila Hasania; M. Anas Anasiru; Misnati Misnati; Novian Swasono Hadi; Indra Domili (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2022)
Adolescents are one of the nutritionally vulnerable groups because adolescents are in a growth or development cycle that requires nutrients in larger amounts than other age groups. Nutritional status is the condition of the body as a result of food consumption and use of nutrients.This study aims to describe the nutritional status and achievement of high school students in Tanggilingo Village, Kabila District, Bone Bolango District. This research method uses a descriptive survey method, namely a survey conducted to describe the variables studied. The population is 46 students and a sample of 30 students. The independent variable is the learning achievement of high school students in Tanggilingo Village, Kabila District, Bone Bolango Regency. The results of the study: 7 students (23.4%) with poor nutritional status, 18 students (60%) with good/normal nutritional status, 4 students (13.3%) with overweight nutritional status and 1 student with obesity nutritional status (3.3%). Student achievement with high report card scores is 20 people (66.4%), moderate report card scores are 9 people (30.3%), and low report card scores are 1 person (3.3%).Most high school students in Tanggilingo Village, Kabila District, Bonebolango Regency have normal nutritional status and high academic achievement.Remaja termasuk salah satu kelompok rentan gizi karena remaja berada pada siklus pertumbuhan atau perkembangan yang memerlukan zat-zat gizi dalam jumlah yang lebih besar dari kelompok umur yang lain, status gizi adalah keadaan tubuh sebagai akibat konsumsi makanan dan pengunaan zat-zat gizi. Penelitian ini bertujuan untuk mengetahui Gambaran Status Gizi Dan Prestasi Siswa Sekolah Menengah Atas Di Desa Tanggilingo Kecamatan Kabila Kabupaten Bone Bolango. Metode penelitian ini menggunakan metode survey deskritif, yaitu survey yang dilakukan untuk menggambarkan variable yang diteliti. Populasi sebanyak 46 siswa dan sampel 30 siswa. Variable mandiri yaitu prestasi belajar siswa sekolah menengah atas di Desa Tanggilingo Kecamatan Kabila Kabupaten Bone Bolango.Siswa dengan status gizi kurang sebanyak 7 siswa (23,4%), status gizi baik/normal sebanyak 18 siswa(60%), status gizi lebih sebanyak 4 siswa (13,3%) dan status gizi obesitas sebanyak 1 siswa (3,3%). Prestasi belajar siswa dengan nilai raport tinggi yaitu 20 orang (66,4%), nilai raport sedang 9 orang (30,3%), dan nilai raport rendah 1 orang (3,3%). Sebagian besar siswa Sekolah Menengah Atas di Desa Tanggilingo Kecamatan Kabila Kabupaten Bonebolango memiliki status gizi yang normal dan prestasi belajar tinggi.